Sierra Leone: Promoting peace or prolonging violence? The duality of the UN Peacekeeping - Vieira, Maurício (2016)
Based on different mechanisms of intervention deployed by the United Nations to intrastate conflicts – peace enforcement, peacemaking, peacekeeping and peacebuilding – it is possible to assume that, in specific cases, the role of the UN in the field contributed to perpetuate the levels of the violence. Such elucidative argument is justified in accordance to the analysis provided in both missions promoted by the institution in Sierra Leone – the United Nations Observer Mission in Sierra Leone, UNOMSIL (1998-1999); and the United Nations Mission in Sierra Leone, UNAMSIL (1999-2005). To discuss this argument and substantiate it, this research was divided into two parts: a critical analysis of both UNOMSIL and UNAMSIL. In each peacekeeping mission, the research focused on a chronological analysis based on the documents published by the both UN missions, such as reports, statements and letters regarding their security, humanitarian, political and economic issues. This division is necessary to understand not only the role of the UN in the field, but how this same international system can influence and also be considered responsible for maintaining and prolonging violent conflicts, while its mission is to promote a world peace.